2022
DOI: 10.3389/fmed.2022.894841
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis in China: A Systematic Review of Cases From 2009–2021

Abstract: Considered the increased threaten of neurosyphilis in China, a review on cases reported in the literature to describe the clinical epidemiological characteristics of neurosyphilis cases, may be beneficial to the early detection and management strategies of neurosyphilis for clinicians. We searched the literature on Chinese neurosyphilis cases published from January 1, 2009 to December 31, 2021, described their clinical epidemiological characteristics and calculated the prevalence of neurosyphilis amongst other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…16 In a systematic review of 149 case reports and 93 retrospective case series, the serological treponemal test positivity was 95% compared to a 75% non-treponemal test positivity rate, and elevated CSF WBCs and proteins were observed in about 70% of the NS patients. 17 Studies reported the specificity of the CSF-TPPA test as 49%-84%, and guidelines vary in recommending this test for NS diagnosis. 18,19 CSF study in our patient showed raised WBCs (427 cells), raised proteins, and reactive CSF-VDRL, favoring a diagnosis of NS.…”
Section: Discussionmentioning
confidence: 99%
“…16 In a systematic review of 149 case reports and 93 retrospective case series, the serological treponemal test positivity was 95% compared to a 75% non-treponemal test positivity rate, and elevated CSF WBCs and proteins were observed in about 70% of the NS patients. 17 Studies reported the specificity of the CSF-TPPA test as 49%-84%, and guidelines vary in recommending this test for NS diagnosis. 18,19 CSF study in our patient showed raised WBCs (427 cells), raised proteins, and reactive CSF-VDRL, favoring a diagnosis of NS.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and timely treatment of neurosyphilis are crucial to preventing irreversible damage to the central nervous system (CNS) [ 5 ]. The clinical spectrum of neurosyphilis in China differs significantly from that in Western countries, where neurological or psychiatric symptoms are the primary indications for performing an LP in syphilis patients [ 18 ]. It is important to note that benzathine penicillin cannot penetrate the blood–brain barrier (BBB) [ 19 ] and symptomatic neurosyphilis can occur even in patients who have received appropriate treatment and have shown a good response [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that nearly half of the studies were conducted in China, we speculate that this may be attributed to the Chinese government's emphasis on the prevention and control of neurosyphilis, which then led to an increase in independent validations of neurosyphilis testing in China. In recent years, the incidence of neurosyphilis has been increasing in China ( 34 , 35 ). A 10-year syphilis control plan was launched by the Chinese government in 2010, meanwhile, due to the irreversibility of neurosyphilis, the Chinese Center for Disease Control has set up a neurosyphilis-specific consortium and established sentinel surveillance for neurosyphilis nationwide ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 10-year syphilis control plan was launched by the Chinese government in 2010, meanwhile, due to the irreversibility of neurosyphilis, the Chinese Center for Disease Control has set up a neurosyphilis-specific consortium and established sentinel surveillance for neurosyphilis nationwide ( 36 ). To present, no VDRL kits in China have received SFDA (State Food and Drug Administration) approval, and the “China National Guidelines for the Diagnosis and Treatment of Syphilis, Gonorrhea and Chlamydia Trachomatis Infection (2020)” suggested the RPR and TRUST for substitute tests ( 34 ). The results of the CSF-FTA-ABS test can be utilized as a diagnostic indicator of neurosyphilis, in accordance with the guidelines for the diagnosis and treatment of syphilis in China, and in the absence of these conditions, the CSF-FTA-ABS test could be substituted with the CSF-TPPA test ( 37 ).…”
Section: Discussionmentioning
confidence: 99%